Stroke in the vascularization area of Percheron artery during treatment of severe pneumonia in a patient with ulcerative colitis - Majda, Urszula; Mida, Magdalena; Michalik, Magdalena; Grzywna-Rozenek, Ewa; Kwiecień, Jarosław; Bąk-Drabik, Katarzyna (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Abstract Stroke is an acute onset neurological event that is entirely vascular in origin. Patients with inflammatory bowel disease are at increased risk of thromboembolic events, and consideration of prophylactic anticoagulation in such patients with additional multiple risk factors seems justified. The aim of this case report was to present a patient with severe ulcerative colitis undergoing biological therapy, who experienced a stroke in the vascularization area of Percheron artery during treatment of septic pneumonia. Due to severe course of ulcerative colitis, he was eligible for biological therapy. During hospitalization for pneumonia, patient developed neurological signs consistent with a stroke, confirmed by magnetic resonance imaging. Further investigations revealed factor von Leiden mutation and patent foramen ovale. Given the rarity of stroke in the pediatric population, early and accurate diagnosis is important to start appropriate treatment as soon as possible.